Electrocardiogram Signal Secure Transmission via a Wireless Communication Protocol of Chaotic Systems Based on Adaptive Sliding Mode Control and Disturbance Observer - Minh Chien Le; Van Nam Giap; Quang Dich Nguyen; Shyh-Chour Huang (IEEE Access, 2023)
This paper presents a new application of the encryption and decryption techniques for securing the electrocardiogram (ECG) signal. The secure communication system (SCS) is embedded two Chen chaotic systems with different initial conditions, which were named master and slave, respectively. An ECG signal is encrypted by using master chaotic system. Which can be sent to the far destination to serving the heath care monitoring process. To obtain the original data, the state of the slave system is used to decrypt the signal. To obtain the goal, the master and slave need to be synchronized. Therefore, to softening the calculation of synchronization control design, the Takagi-Sugeno fuzzy (TSF) was used to remodel the master and slave into the fuzzy format, which are consists of the sublinear systems and fuzzy outer membership functions. Second, the disturbance observer (DOB) was proposed on slave system, which is used to reject the parameters variations and disturbances during the transmission. Third, the sliding mode control (SMC) was designed to synchronize the master and slave systems. Fourth, the stability of SCS is proved based on the Lyapunov condition. Finally, the simulation by using MATLAB software on computer and experiment by using the WIFI microchip ESP8266 were provided to show the power of the proposed methods.